2014
DOI: 10.1038/nm.3655
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of JAK-STAT signaling stimulates adult satellite cell function

Abstract: Diminished regenerative capacity of skeletal muscle occurs during adulthood. We identified a reduction in the intrinsic capacity of murine adult satellite cells to contribute to regeneration and repopulate the niche. Gene expression analysis identified an increase in expression of JAK/STAT signaling targets between 3 week old and 18 month old mice. Knockdown of Jak2 or Stat3 significantly stimulated symmetric satellite stem cell divisions on cultured myofibers. Knockdown of Jak2 or Stat3 in prospectively isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
410
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 334 publications
(430 citation statements)
references
References 49 publications
12
410
3
1
Order By: Relevance
“…The discovery of murine MuSCs capable of robustly regenerating and restoring strength to injured muscles (1,3,7,(16)(17)(18)(19), and a means for their expansion in culture using inducers such as p38 MAPK inhibitors, has provided a framework for their future clinical application (22,(51)(52)(53). Moreover, recent strides in the isolation and characterization of their human counterparts from tissues or as derivatives from human embryonic stem (ES) or induced pluripotent stem (iPS) cells (54-59) now facilitate the use of these potent cell types as a muscle cell therapeutic.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of murine MuSCs capable of robustly regenerating and restoring strength to injured muscles (1,3,7,(16)(17)(18)(19), and a means for their expansion in culture using inducers such as p38 MAPK inhibitors, has provided a framework for their future clinical application (22,(51)(52)(53). Moreover, recent strides in the isolation and characterization of their human counterparts from tissues or as derivatives from human embryonic stem (ES) or induced pluripotent stem (iPS) cells (54-59) now facilitate the use of these potent cell types as a muscle cell therapeutic.…”
Section: Discussionmentioning
confidence: 99%
“…CD44 activated by ligand binding is internalized and elicits STAT3 (signal transducer and activator of transcription 3) acetylation (47). Price et al (48) currently reported that JAK-STAT3 signaling triggered the myogenic differentiation through cyclin D1 promoter. Despite short time expression of TSG6 in MSCs, the SHAP-HA complex remained longer in the transplanted area suggesting that the SHAP-HA complex may play a role in myogenic differentiation of MSCs (see fetal actin-stained muscle fibers in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that inhibition of the IL-6 intracellular mediator, namely the Jak/Stat pathway, stimulates muscle regeneration in both aged and dystrophic mice [60,61].…”
Section: Inflammationmentioning
confidence: 96%